Towards Identifying the Dynamics of Sliding by Acoustic Emission and Vibration - Korchuganov M. A. Maksim Anatolievich; Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Podgornykh O. A. Oleg Anatolievich; Shamarin N. N. Nikolay Nikolaevich; Filippova E. O. Ekaterina Olegovna (2016, 2016)
Title screen